2023
DOI: 10.3102/01623737221141415
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Implementation of Michigan’s Partnership Model of School and District Turnaround: Mixed-Methods Evidence From the First 2 Years of Reform Implementation

Abstract: The recent Every Student Succeeds Act (ESSA) requires states to identify and turn around their lowest performing schools, but it breaks somewhat from prior policies by granting states significant autonomy over how they identify and turn around these schools. This mixed-methods study, which draws on administrative, qualitative, and survey data, examines the effectiveness of Michigan’s approach to school turnaround under ESSA. We find that students in turnaround schools experienced significant achievement gains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…This study shows that the Partnership Model has some merit as an approach to turnaround (Burns et al, 2023). Most of the leaders we interviewed expressed satisfaction with the supports and resources provided by the state, and they generally appreciated having some flexibility to create their own goals and plans.…”
Section: Discussionmentioning
confidence: 89%
“…This study shows that the Partnership Model has some merit as an approach to turnaround (Burns et al, 2023). Most of the leaders we interviewed expressed satisfaction with the supports and resources provided by the state, and they generally appreciated having some flexibility to create their own goals and plans.…”
Section: Discussionmentioning
confidence: 89%
“…Stone (1989) suggested that mechanistic and inadvertent causes were potentially weaker in terms of assigning blame and advocating for one's position and implied less resistance or pushback against the policy. This suggestion was reflected in Partnership leaders' generally positive feelings about the policy and the supports it offered (Burns et al, 2023) and implied the possibility of less resistance to and greater longevity for the reform compared to policies that might be more contentious (for example, school closure). Still, the actual supports the policy offered (e.g., modest 21H grant funding, the call for community Partnerships unfunded by the state, MDE liaisons) were not generally aligned with participants' diagnostic and prognostic frames.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of action behind the Partnership reform involved providing a variety of resources to identified districts and schools and asking them to craft a 3-year strategic plan with measurable achievement goals. These resources included some grant funding that districts could apply for along with community partnerships and technical assistance providers (Burns et al, 2023). The SEA is an important component of this assistance.…”
Section: Policy Contextmentioning
confidence: 99%